IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT(CRM) PADA TOKO ROTI GANDA BERBASIS WEB - Yosua Oliver Siallagan; Naiksin Fandier Saragih; Jhoni Maslan Hutapea (Universitas Methodist Indonesia, 2020)
Competition in the business world in the era of globalization is now getting stronger. For that, a business requires a system that works efficiently and effectively. The Ganda Bakery is one of Pematang Siantar's special culinary delights which is well known among the people in the city and outside the city. Double Bakery is a legendary bakery that has existed since 1979 which is very crowded and in demand by people in the city and outside the city. Due to the large number of customers who come to the Double Bread Shop, so many new bakeries are trying to provide types of bread that resemble the menu in the Ganda Roti Shop, so that many new bakery businesses are opening to compete for customers at the Ganda Roti Shop. Therefore, by looking at the conditions and problems at the Ganda Bakery, it is necessary to have a media in the form of an online-based system to integrate ordering, marketing, and customer service that can manage the relationship between the company and its customers by creating applications with the CRM concept. In this study using the User-Centered Design (UCD) method is a new paradigm in the development of web-based systems. The purpose of using this UCD method is to overcome the problem of the user's inability to use the system, and it is hoped that the user will be able to know the function of the system only in one use. The UCD method involves potential users in the early stages of development so that potential users can provide input regarding the e-commerce system interface. The final result in building e-commerce is expected to produce maximum appearance and functionality and have usability values. So that UCD is very suitable to be used in developing and building systems effectively and efficiently at the Double Bakery.